2020
DOI: 10.1021/acscatal.0c02228
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Monoacylation of Symmetrical Diamines and Its Application to the Synthesis of Pharmaceutically Relevant Amides

Abstract: Monoacylated diamines are common motifs present in pharmaceuticals, agrochemicals, and natural products. However, the synthesis of these compounds often requires selective protection/deprotection steps leading to waste and poor atom economy. Here we describe the truncation of a carboxylic acid reductase (CAR) yielding an adenylation domain capable of selective amide bond formation under aqueous conditions. This truncated construct had a higher amidation activity compared to the full-length enzyme. The amidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 31 publications
0
35
0
1
Order By: Relevance
“…In einer Folgestudie wurde dieses Konzept weiter verschlankt, indem eine verkürzte CAR-Variante,d ie ledig- ). [222] Obwohl das Substratspektrum und die schwierige Handhabung aufgrund ihrer schwachen Expression und Lçslichkeit die Nutzung einschränken, erhalten Amidsynthetasen zunehmende Bedeutung fürd ie späte Modifizierung. Wessjohann und Coautoren berichteten über die homologen Amidsynthetasen CloL, SimL und CouL, die zur Modifikation von Aminocumarinen (217)i ne inem modularen Verfahren geeignet waren.…”
Section: Methodsunclassified
“…In einer Folgestudie wurde dieses Konzept weiter verschlankt, indem eine verkürzte CAR-Variante,d ie ledig- ). [222] Obwohl das Substratspektrum und die schwierige Handhabung aufgrund ihrer schwachen Expression und Lçslichkeit die Nutzung einschränken, erhalten Amidsynthetasen zunehmende Bedeutung fürd ie späte Modifizierung. Wessjohann und Coautoren berichteten über die homologen Amidsynthetasen CloL, SimL und CouL, die zur Modifikation von Aminocumarinen (217)i ne inem modularen Verfahren geeignet waren.…”
Section: Methodsunclassified
“…Thea uthors showed that CARmm-A performs selective mono-acylation of diamines without the need for protecting groups.Anarray of carboxylic acids with loadings up to 10 mm was utilised in af acile one-step amidation yielding various amides (208)(209)(210)(211)(212)(213)(214)(215)(216), e.g.,t he vasodilator cinepazide (216,Scheme 36 b). [222] Despite their current narrow substrate scope and difficult handling due to weak expression and solubility,a mide bond forming synthetases are receiving increased attention for latestage modification. Wessjohan and co-authors reported on the homologous amide synthetases CloL, SimL, and CouL utilised in am odular fashion to modify aminocoumarin (217).…”
Section: Direct Amide Bond Formation:e Xamples and Recentmentioning
confidence: 99%
“…An array of carboxylic acids with loadings up to 10 m m was utilised in a facile one‐step amidation yielding various amides ( 208 – 216 ), e.g., the vasodilator cinepazide ( 216 , Scheme 36 b ). [222] …”
Section: Selective Enzyme‐catalysed Amide Bond Formationmentioning
confidence: 99%
“…Notable exceptions to the use of purified proteins and/or whole‐cells to drive ATP regeneration from AMP were exemplified by the synthesis of a range of pharmaceutically relevant amides in water using the adenylation domain of a carboxylic acid reductase, [74] the preparation of the Cbz‐protected 4‐formyl piperidine aldehyde 36 [75] and by the selective reduction of 4‐methoxybenzoic acid 46 to 4‐methoxybenzaldehyde 47 using CAR, [36] where either cell‐free extracts or lyophilised cell‐free extracts were employed.…”
Section: Application Of Polyphosphate Kinasesmentioning
confidence: 99%